COMPARATIVE STUDY OF PIGMENTS ON REGENERANTS FROM IN VITRO AND SPONTANEOUS FLORA OF THYMUS sp. - ANA M. ROŞU; ROXANA E. VOICU; DANIELA NICUŢĂ (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This paper presents the quantitative determination of pigments extract of Thymus sp. from in vitro culture and spontaneous flora. For in vitro culture were used phytohormones (indoleacetic acid-IAA, indole-3-butyric acid-IBA and benzylaminopurine-BAP) in order to obtain a high yield in development of Thymus sp. plants. The source of spontaneous flora of Thymus sp. was Bacau (Magura), Romania. The biochemical investigations realised on Thymus sp. using Thin Layer Chromatography and the UV-Vis spectrophotometry showed that the production of assimilating pigments is influenced by growth and lighting conditions of plants.